MODIFIKASI MEKANISME PENENTUAN PENJADWALAN JOB PADA METODE DANNENBRING - Hendy Tannady (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2013)
Scheduling methods particularly in scheduling a job toward machine capacity is often not optimal in generating the minimum makespan time due to the inappropriate mechanism of determining the schedule from the job. By using an appropriate mechanism on the local search for both of the job order towards machine and the recapitulation of the makespan in each job in order to produce the optimal scheduling is proved an effective approach to minimize the error of the end time processes that are too long. This approach is also able to provide the optimal solution for the work planning. This research focuses on the searching for some mechanism design alternatives in job scheduling by employing the makespan recapitulation table of each job on the machine determined by Dannenbring method. The result of this research shows that the smallest possible makespan time is 93, by following the order of job j1-j7-j2-j8-j4-j5-j6-j3, j1-j6-j2-j7-j8-j4-j5-j3 and j1-j6-j2-j4-j8-j7-j5-j3 using hybrid Pi1 earlier mechanism and hybrid Pi2 earlier mechanism.